Characterization of young and aged ferrets as animal models for SARS-CoV-2 infection with focus on neutrophil extracellular traps - Pilchová, Veronika; Gerhauser, Ingo; Armando, Federico; Wirz, Katrin; Schreiner, Tom; de Buhr, Nicole; Gabriel, Gülşah; Wernike, Kerstin; Hoffmann, Donata; Beer, Martin; Baumgärtner, Wolfgang; von Köckritz-Blickwede, Maren; et al. (Frontiers in Immunology, 2023)
Neutrophil extracellular traps (NETs) are net-like structures released by activated neutrophils upon infection (e.g. SARS-CoV-2) as part of the innate immune response that have protective effects by pathogen entrapment and immobilization or result in detrimental consequences for the host due to massive release of NETs and their impaired degradation by nucleases like DNase-1. Higher amounts of NETs are associated with COVID-19 severity and are a risk factor for severe disease outcome. The objective of our study was to investigate NET-formation in young versus aged ferrets to evaluate their value as translational model for SARS-CoV-2-infection and to correlate different NET-markers and virological parameters. In each of the two groups (young and aged), nine female ferrets were intratracheally infected with 1 mL of 10^6 TCID50/mL SARS-CoV-2 (BavPat1/2020) and euthanized at 4, 7 or 21 days post infection. Three animals per group served as negative controls. Significantly more infectious virus and viral RNA was found in the upper respiratory tract of aged ferrets. Interestingly, cell-free DNA and DNase-1 activity was generally higher in BALF, but significantly lower in serum of aged compared to young ferrets. In accordance to these data, immunofluorescence microscopy revealed significantly more NETs in lungs of aged compared to young infected ferrets. The association of SARS-CoV-2-antigen in the respiratory mucosa and NET markers in the nasal conchae but absence of virus antigen in the lungs, confirm the nasal epithelium as major location for virus replication as described for young ferrets. Furthermore, a strong positive correlation was found between virus shedding and cell-free DNA or the level of DNAse-1 activity in aged ferrets. Despite the increased NET formation in infected lungs of aged ferrets, the animals did not show a strong NET phenotype and correlation among tested NET markers. Therefore, ferrets are of limited use to study SARS-CoV-2 pathogenesis associated with NET formation. Nevertheless, the mild to moderate clinical signs, virus shedding pattern and the lung pathology of aged ferrets confirm those animals as a relevant model to study age-dependent COVID-19 pathogenesis.